Isolation of multiple plant growth-promoting fungi and their effect on rice growth improvement on non-grain converted land - Li, Xuqing; Ren, Xiaoxu; Chen, Han; Xin, Yukang; Zhou, Tiefeng; Yan, Jianli; Xu, Jun; Ijaz, Munazza; Ahmed, Temoor; Li, Bin; Ali, Qurban (Frontiers in Plant Science, 2025)
IntroductionLand cultivation is the cornerstone of national food security. However, with the development of non-grain production on cultivated land, China has to use less cultivated land to feed a larger population of the world. To effectively resolve issues caused by non-grain production on cultivated land, Zhejiang Province has initiated efforts to restore non-grain-converted land back to grain cultivation. Whereas, the discovery and application of plant growth-promoting fungi (PGPF) can offer promising solutions to these challenges.MethodsPGPF was isolated and identified from soil converted from non-grain lands based on bioassays for plant growth promoting traits, and then their impacts on soil properties and microbial community structure were also investigated.ResultsIn this study, 15 fungal isolates from 108 soil samples were considered as potential PGPF due to their ability to solubilize phosphate (11.91 to 31.65 mm), produce both siderophores (17.09 to 24.66 mm) and indole-3-acetic acid (8.79 to 50.23 μg/mL or 36.72 to 96.50 μg/mL). Results of in vivo assays showed that isolates TL-B31f and FY-R41f could cause a great increase in plant height (15.30% and 13.84%), root length (33.62% and 43.31%), seedling fresh weight (78.58% and 89.77%) and dry weight (9.31% and 28.12%) of rice compared to the control. Based on morphological and molecular analyses, isolates TL-B31f and FY-R41f were identified as Aspergillus tubingensis and Talaromyces veerkampii, respectively. Furthermore, after 55 days of inoculation with the two isolates, the soil content of available phosphate was significantly increased by 42.52% and 48.51%, respectively, compared to the control. In addition, high-throughput sequencing analysis showed that compared with the control, the microbial community composition of the two isolates treatments was reconstructed by increasing or decreasing some specific microbes, while soil properties, such as pH, soil organic matter (SOM), total phosphorus (TP), and available phosphate (AP) might play important roles in modulating rice growth by influencing the composition of microbial communities.ConclusionsOverall, our findings highlight the potential of these isolates to be developed into novel biofertilizers for crop growth in non-grain lands.